2021
DOI: 10.1001/jamahealthforum.2021.4044
|View full text |Cite
|
Sign up to set email alerts
|

Association of Prenatal Care Services, Maternal Morbidity, and Perinatal Mortality With the Advanced Maternal Age Cutoff of 35 Years

Abstract: IMPORTANCE Maternal and perinatal mortality remain high in the US despite growing rates of prenatal services and spending, and little rigorous evidence exists regarding the impact of prenatal care intensity on pregnancy outcomes. Patients with an expected date of delivery just after their 35th birthday may receive more intensive care owing to the advanced maternal age (AMA) designation; whether this increase in prenatal care is associated with improvements in outcomes has not been explored. OBJECTIVETo determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 38 publications
1
11
0
Order By: Relevance
“…For instance, women aged 35–39 years had the highest likelihood of receiving antenatal care visits, care from skilled antenatal care providers, while women aged over 40 years had the highest likelihood of receiving skilled birth assistance and accessing facility-based delivery. This finding is consistent with earlier studies conducted in the USA and Mexico ( 29 , 30 ).…”
Section: Discussionsupporting
confidence: 94%
“…For instance, women aged 35–39 years had the highest likelihood of receiving antenatal care visits, care from skilled antenatal care providers, while women aged over 40 years had the highest likelihood of receiving skilled birth assistance and accessing facility-based delivery. This finding is consistent with earlier studies conducted in the USA and Mexico ( 29 , 30 ).…”
Section: Discussionsupporting
confidence: 94%
“…This is consistent with previous studies that have shown an association between inadequate prenatal care utilization with low levels of education, poor social support, unplanned pregnancy, and poverty, 26 and that higher education is protective 27 . Additionally, a study in the USA showed that perinatal outcomes were better for pregnant women just over the 35‐year cut‐off when compared with those just under this age, suggesting that the additional age‐related pregnancy monitoring may play a role in improving outcomes 5 . Together these studies highlight that many factors influence utilization of prenatal services.…”
Section: Discussionmentioning
confidence: 98%
“…Widespread use of family planning, postponing pregnancy because of education or career goals, and advances in assisted reproductive technology contribute to pregnancy later in life 4 . Prenatal care is important for a healthy pregnancy and birth outcomes, especially for older women 5 . Enhanced prenatal care that includes additional monitoring during pregnancy and birth is recommended for women over the age of 35 years due to associated health risks 6 .…”
Section: Introductionmentioning
confidence: 99%
“…Consistent with prior research, individuals were required to meet one of the following requirements on the date of delivery: (1) two unique delivery‐related diagnosis codes, (2) two unique delivery‐related procedure codes, or (3) one delivery‐related diagnosis and one delivery‐related procedure code. 10 , 11 Dates with two or more delivery‐related diagnosis and/or procedure codes within 100 days of each other were grouped together and the date with the greatest number of diagnosis and/or procedure codes was flagged as the date of delivery. When an individual had more than one birth episode during the study period (3% of births), we randomly chose one birth to maintain the independence of observations.…”
Section: Methodsmentioning
confidence: 99%